2014
DOI: 10.1523/jneurosci.3965-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ON Cone Bipolar Cell Subtypes in Temporal Coding in the Mouse Retina

Abstract: In the visual system, diverse image processing starts with bipolar cells, which are the second-order neurons of the retina. Thirteen subtypes of bipolar cells have been identified, which are thought to encode different features of image signaling and to initiate distinct signal-processing streams. Although morphologically identified, the functional roles of each bipolar cell subtype in visual signal encoding are not fully understood. Here, we investigated how ON cone bipolar cells of the mouse retina encode di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 133 publications
(36 reference statements)
4
112
1
1
Order By: Relevance
“…A recent study revealed distinct postsynaptic temporal processing characteristics of different ON bipolar cell types (Ichinose et al 2014). Experiments combining light responses and current injection suggested that low-pass characteristics (i.e., suppression of high temporal frequencies) depended on intrinsic properties of the bipolar cells, whereas high-pass characteristics (i.e., suppression of low temporal frequencies) were generated through synaptic mechanisms.…”
Section: Parallel Excitatory Pathways Are Established At the First Rementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed distinct postsynaptic temporal processing characteristics of different ON bipolar cell types (Ichinose et al 2014). Experiments combining light responses and current injection suggested that low-pass characteristics (i.e., suppression of high temporal frequencies) depended on intrinsic properties of the bipolar cells, whereas high-pass characteristics (i.e., suppression of low temporal frequencies) were generated through synaptic mechanisms.…”
Section: Parallel Excitatory Pathways Are Established At the First Rementioning
confidence: 99%
“…The nonlinearity of glutamate release is most striking in laminae near the middle of the IPL, adjacent to the boundary between ON and OFF layers (Roska & Werblin 2001, Baden et al 2013, Borghuis et al 2013, Ichinose et al 2014). Because each bipolar cell subunit is small, it is stimulated by high spatial frequencies; the independent activity of each subunit endows the postsynaptic ganglion cell with sensitivity to fine spatial patterns (Demb et al 2001, Baccus et al 2008, Schwartz et al 2012).…”
Section: Parallel Excitatory Pathways Are Established At the First Rementioning
confidence: 99%
“…To achieve such presynaptic balance, glutamate release from bipolar cells onto DSGCs must be curbed until stimuli are sufficiently strong to evoke GABA release from starbursts. This is thought to be accomplished by using high- and low-sensitivity bipolar cells (Ichinose et al, 2014; Odermatt et al, 2012; Poleg-Polsky and Diamond, 2016b) to independently drive starbursts and DSGCs, in a way that compensates for the starburst's threshold non-linearity (Figure 1A & B) (Poleg-Polsky and Diamond, 2016b). As this model requires the matching of presynaptic GABA/glutamate/ACh signals, we refer to it as the ‘matched’ model for DS in ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental techniques were similar to those described previously (13,14). The eyes were placed in a cooled oxygenated dissecting solution containing 115 mM NaCl, 2.5 mM KCl, 2.5 mM CaCl 2 , 1.0 mM MgCl 2 , 10 mM HEPES, and 28 mM glucose, and were adjusted to pH 7.4 with NaOH.…”
Section: Methodsmentioning
confidence: 99%